Export volatility and corporate financing decisions in Australia: a dynamic panel data approach - Chow, Yee Peng; Muhammad, Junaina; Amin Noordin, Bany Ariffin; Cheng, Fan Fah (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
This paper investigates the influence of export volatility on corporate financing decisions of a sample of non-financial firms listed on the Australian Securities Exchange over the period 2004-2014. The GARCH model is employed to model export volatility. Using a dynamic panel data method, namely the robust two-step system GMM estimation procedure, the results show that export volatility has a significant negative effect on the financing decisions of Australian firms. The results also reveal that while long-term debt is affected by export volatility, similar observation does not hold for short-term debt. This indicates that Australian firms are chiefly concerned about the adverse effect of export volatility in the long-run. The results also provide evidence of the importance of accounting for the effects of the Global Financial Crisis. Policy implications are derived from the findings.